Question Number 166542 by abdurehime last updated on 22/Feb/22
Answered by Rasheed.Sindhi last updated on 22/Feb/22
$${n}\left({A}\right)=\left(\mathrm{2}{x}+{y}\right)+\left({x}+{y}\right)=\mathrm{3}{x}+\mathrm{2}{y}=\mathrm{13} \\ $$$${n}\left({B}\right)=\left(\mathrm{3}{y}−{x}\right)+\left({x}+{y}\right)=\mathrm{4}{y}=\mathrm{8} \\ $$$${y}=\mathrm{8}/\mathrm{4}=\mathrm{2}\Rightarrow\mathrm{3}{x}+\mathrm{2}\left(\mathrm{2}\right)=\mathrm{13}\Rightarrow{x}=\mathrm{3} \\ $$$$\left({a}\right)\:{n}\left({A}\cup{B}\right)=\left(\mathrm{2}{x}+{y}\right)+\left({x}+{y}\right)+\left(\mathrm{3}{y}−{x}\right) \\ $$$$\:\:\:\:\:\:\:=\mathrm{2}{x}+\mathrm{5}{y}=\mathrm{2}\left(\mathrm{3}\right)+\mathrm{5}\left(\mathrm{2}\right)=\mathrm{16} \\ $$$$\left({b}\right)\:{n}\left({U}\right)=\mathrm{16}+\left(\mathrm{2}{x}−{y}\right)=\mathrm{16}+\mathrm{2}\left(\mathrm{3}\right)−\mathrm{2}=\mathrm{20} \\ $$$$\left({c}\right)\:{n}\left({B}−{A}\right)=\mathrm{3}{y}−{x}=\mathrm{3}\left(\mathrm{2}\right)−\mathrm{3}=\mathrm{3} \\ $$$$\left({d}\right)\:{n}\left({A}\cap{B}\:'\:\right)=? \\ $$$$\:\:\:\:{n}\left({A}\cap{B}\:'\right)={n}\left({A}−{B}\right)=\mathrm{2}{x}+{y}=\mathrm{2}\left(\mathrm{3}\right)+\mathrm{2}=\mathrm{8}\:\:\:\:\: \\ $$
Commented by abdurehime last updated on 22/Feb/22
$$\mathrm{Thanks} \\ $$
Commented by abdurehime last updated on 22/Feb/22
$$\mathrm{is}\:\mathrm{c}\:\mathrm{correct}?? \\ $$
Commented by Rasheed.Sindhi last updated on 22/Feb/22
$${I}'{ve}\:{corrected}\:{it}\:{now}. \\ $$